2000
DOI: 10.1002/(sici)1097-0185(20000301)258:3<252::aid-ar4>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Colloid in the pituitary pars distalis of viscacha (Lagostomus maximus maximus): Ultrastructure and occurrence in relation to season, sex, and growth

Abstract: Randomly distributed extracellular colloidal accumulations were observed in the pars distalis of viscacha (Lagostomus maximus maximus). They were preferentially located in the peripheral zone of the gland and showed variability in shape and size. Two different types of colloidal accumulations were found by electron microscopy: 1) those surrounded by nongranulated follicular cells that correspond to characteristic follicles, and 2) those surrounded by granulated cells. In the follicles lined by nongranulated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
(38 reference statements)
1
24
0
Order By: Relevance
“…It is important to note that the follicles observed in the PT have characteristics similar to those described in the PD and PI of the same rodent in previous studies, in which we demonstrated the presence of glycoproteins (Scardapane et al, 1983) and the dependence of the number of follicles on the functional state of the gland (Mohamed et al, 2000). Kameda (1990) described the presence of follicles in the guinea pig PT and their modifications with age, suggesting a physiological role for these structures.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is important to note that the follicles observed in the PT have characteristics similar to those described in the PD and PI of the same rodent in previous studies, in which we demonstrated the presence of glycoproteins (Scardapane et al, 1983) and the dependence of the number of follicles on the functional state of the gland (Mohamed et al, 2000). Kameda (1990) described the presence of follicles in the guinea pig PT and their modifications with age, suggesting a physiological role for these structures.…”
Section: Discussionsupporting
confidence: 81%
“…In our laboratory, studies have been conducted to determine the structural and ultrastructural characteristics of hypophyseal PD and pars intermedia (PI) (Scardapane et al, 1983;Mohamed et al, 1995). These two hypophyseal regions are characterized by the presence of follicular structures with colloidal material in the lumen and extracellular accumulation of colloid, which probably stores hormonal products (Mohamed et al, 2000). The viscacha has a seasonal reproductive cycle (Fuentes et al, 1991), with important participation of the pineal gland (Dominguez et al, 1987;Cernuda-Cernuda et al, 2003).…”
mentioning
confidence: 99%
“…Previous studies demonstrated that the pineal gland and its hormone, melatonin, are involved in its reproductive rhythmicity (Domínguez et al, 1987;Fuentes et al, 1991;Pelzer et al, 1999;Muñ oz et al, 1999Muñ oz et al, , 2001Mohamed et al, 2000). Lascano et al (1999) demonstrated an avascular, rod-rich retina, with a specialized region spanning through most of the equator of the eye of the viscacha, suggesting that this equatorial region could be a highly sensitive light detector related to foraging behaviors during crepuscular or nocturnal hours.…”
mentioning
confidence: 98%
“…There are randomly distributed extracellular colloidal accumulation were observed in the pars distalis of Viscacha (Lagostomus maximus maximus) located in the peripheral zone of the gland and showed variability in shape and size [10]. In vespertilionid bat, Scotophilus heathi the electron microscopic studies revealed six distinct cells…”
Section: Introductionmentioning
confidence: 99%